The extent to which the last decade has yielded additional treatment options for EGFR-associated rash besides classic treatment with antibiotics and corticosteroids - A systematic review - Papoui, Eleni; Papastavrou, Evridiki; Merkouris, Anastasios; Charalambous, Andreas (My University, 2021)
Purpose: To investigate the effectiveness of different interventions for the prevention and treatment of EGFRI treatment-induced rash (EGFRIr) that appeared in the last decade, excluding antibiotics and steroids products alone. Method: A systematic review was performed in 2019 and was updated in 2020. The search strategy was limited to studies published within the last 10 years on the Medline database accessed via Pubmed and the Cochrane database. The search was performed using keywords combined with AND, OR. Results: The search yielded thirteen studies. The studies were divided into two categories, based on the intervention method used: four studies used creams containing vitamin K1 or vitamin K3 (henceforth classified as “Category A″) and nine studies (“Category B″) focused on different intervention methods such as laser treatment, Polydatin (PD) cream treatment, treatment with sunscreen, Adapalene gel treatment, topical aloe vera treatment, topical hydration treatment, the impact of a pre-emptive skin treatment and, finally, epidermal growth factor (EGF) ointment treatment. From “Category A″, the results vary as two studies found no benefit from cream use, while two studies indicated a possible improvement on skin reactions from cream use. In “Category B″, a benefit due to laser treatment was indicated, Polydatin-containing moisturizer showed a reduction in the incidence of rash grade ≥ II in patients treated with afatinib, while treatment with sunscreen demonstrated no benefit for the prevention of EGFRIr. Additionally, Adapalene gel use is not recommended as prophylaxis for EGFRIr, topical aloe vera may be used in the management for EGFRIr due to cetuximab, topical hydration resolved the EFGRIr, the pre-emptive skin treatment routine was well tolerated and the epidermal growth factor ointment improved all the symptoms due to EGFRI. Conclusions: The results from the studies vary, although this study focuses on reviewing treatment interventions that can be utilized, apart from antibiotics and steroids, in order to alleviate the problems of the patients suffering from EGFRIr. More specifically, the authors of this review cannot draw a conclusion from “Category A″, as the efficacy of vitamin K for the management of EGFRIr is controversial. From “Category B″, some of the suggested treatments show encouraging results, while others may prove ineffective and rather harmful for the patients.
Keywords: EGFR; Prevention; Rash; Treatmant; Vitamin K1/K3